Mast cell activation: A complex interplay of positive and negative signaling pathways. Issue 9 (22nd August 2014) - Sibilano, Riccardo; Frossi, Barbara; Pucillo, Carlo E.
<x xml:space="preserve">Abstract</x> Mast cells regulate the immunological responses causing allergy and autoimmunity, and contribute to the tumor microenvironment through generation and secretion of a broad array of preformed, granule‐stored and de novo synthesized bioactive compounds. The release and production of mast cell mediators is the result of a coordinated signaling machinery, followed by the FcεRI and FcγR antigen ligation. In this review, we present the latest understanding of FcεRI and FcγR signaling, required for the canonical mast cell activation during allergic responses and anaphylaxis. We then describe the cooperation between the signaling of FcR and other recently characterized membrane‐bound receptors (i.e., IL‐33R and thymic stromal lymphopoietin receptor) and their role in the chronic settings, where mast cell activation is crucial for the development and the sustainment of chronic diseases, such as asthma or airway inflammation. Finally, we report how the FcR activation could be used as a therapeutic approach to treat allergic and atopic diseases by mast cell inactivation. Understanding the magnitude and the complexity of mast cell signaling is necessary to identify the mechanisms underlying the potential effector and regulatory roles of mast cells in the biology and pathology of those disease settings in which mast cells are activated.